Promising modern data processing algorithms - Hrama, Mykhailo (My University, 2026)
The world is suffering from data overload. For years, we have tried to solve this problem with step-by-step logic. Now, these technologies cannot effectively solve problems with large amounts of data. We have moved far beyond simple spreadsheets. Today, we need systems that can process noise in real time, catching patterns as they emerge. It’s not just about getting a faster processor; it’s about changing the way machines see everything around them. Світ страждає від перевантаження даними. Роками ми намагалися вирішити цю проблему за допомогою покрокової логіки. Тепер ці технології не можуть ефективно вирішувати проблеми з великими обсягами даних. Ми вийшли далеко за рамки простих електронних таблиць. Сьогодні нам потрібні системи, які можуть обробляти шум у режимі реального часу, вловлюючи закономірності в міру їх виникнення.
Keywords: кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; machine learning; big data; машинне навчання; великі дані